Silence Speaks: The Relationship between Immigration and the Underreporting of Crime. (July 2017) - Gutierrez, Carmen M.; Kirk, David S.
Scarce in criminological literature is an exploration of whether crime reporting varies geographically. Yet, there are substantive reasons to believe not only that the percentage of crimes reported to the police varies across jurisdictions but also that crime reporting can be explained by ecological characteristics. Drawing upon data from both the National Crime Victimization Survey and the U.S. census, this study examines the relationship between immigration and the likelihood that crimes are reported to the police. Results indicate that crime reporting is inversely related to increases in the relative size of both the noncitizen and foreign-born populations within a metropolitan area, and that the negative effect is greater for violence than for property crime. Implications for the underreporting of crime are discussed.